EVALUASI KEPUASAN PENGGUNA TERHADAP KEBIJAKAN PENGEMBANGAN KOLEKSI BUKU PERPUSTAKAAN STMIK STIKOM INDONESIA - Anindyatari, Ida Ayu Gede; Kastawa, Made; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT             The purpose of this research is to determine the satisfaction level users of the library book collection development policy STMIK STIKOM Indonesia. This research is quantitative descriptive research and the techniques of data collection  used questionnaires, literature, and observation. The subjects of this research were all visitors of STMIK STIKOM Indonesia library. The population is all library visitors in February 2016 which are totally 304 people and pointed 173 as sample became respondents. The technique of sampling is using Proportionate Stratified Random Sampling. This research are conducted for one month in March 2016. The results of this research is the book collection development activity of library STMIK STIKOM Indonesia are carried out routinely and it has been considered in accordance with the need of users, but has not been fulfilled need of the library users, with an average  63.17% of user satisfaction rate. Keywords: user satisfaction, library collection,college library